STRATEGY OF MARKET SEGMENTATION, TARGETING AND POSITIONING IN INCREASING THE NUMBER OF CUSTOMERS AT PT. BANK MUAMALAT INDONESIA Tbk KCP PANYABUNGAN - rosdiyah rosdiyah; abdul nasser hasibuan; azwar hamid; zulaika matondang (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This research is motivated by the large number of people in the city of Panyabungan who are predominantly Muslim who will provide benefits for Islamic banks. Selection of the right market by using market segmentation strategies, targeting and positioning that will help PT. Bank Muamalat Indonesia Tbk KCP Panyabungan in selecting potential customers who are useful to win competition with other banks. The research methodology used is descriptive qualitative using primary data and secondary data. Primary data were obtained by collecting data through interviews and observations, while secondary data were obtained from documents of BMI KCP Panyabungan. The research found that the marketing strategy for BMI KCP Panyabungan products was market segmentation by selecting demographic and behavioral segmentation. Then the targeting is that BMI KCP Panyabungan chooses traders, entrepreneurs and employees as the target market. Next to positioning, BMI KCP Panyabungan builds a good image by embracing Ulama and educating the public that PT. Bank Muamalat Indonesia is an Islamic bank and is free from usury and provides souvenirs containing symbols to Ulama. Meanwhile, the obstacles faced are the size of the area, other competitors.